Specific Nature of the Status of a European Union Official Compared to National Officials - Jaworski, Bartłomiej (University of Wroclaw. Faculty of Law, Administration & Economics, 2016)
The emergence of European Union (EU) structures and their ongoing development has led to a visible strengthening of the status of the European Union administration officials. This is due to the European Union broadening the scope of its tasks and an increasingly higher level of complexity of the matters that the European Union engages with (directly or indirectly). As a result, there is a significant discrepancy between the status of an EU administration official and a national one. The latter does not enjoy as many privileges as the former. Thus, in spite of analogies evident between the two types of officials, there are also notable differences that stem indirectly from the systems of administration in which they function. The following paper attempts to explain the causes for similarities and differences between the status of administration officials of the EU and their national counterparts. It also specifically focuses on the status of an EU administration official.
Keywords: European Union; administration officials